PRASEJARAH INDONESIA: Tinjauan Kronologi dan Morfologi - Slamet Sujud Purnawan Jati (Jurnal Sejarah dan Budaya, 2013)
Abstract: Significance of Indonesia prehistory study is used to discover reconstruction a whole past human life aspects before to history era through the material remains have left behind (artifacts, ecofacts, and fitures). The life aspects are such as environmental, ancient man, technology, social life, economy, and culture. Through chronological and morphological studies, it is can be understood early development of Indonesian societies and culture in prehistoric period according to the time, its characteristic, man variety, and material remains.